Determinants of Bank Profitability in the United States - BA, ZIWEI (2019)
Abstract This paper examines determinants of commercial bank profitability in the United States over the period 2009 to 2018. The sample in this paper is 100 commercial, active and lived banks located in the US and it contains 1000 observations due to creating a balanced dataset. ROAE as a measure of profitability is used in this paper, and we choose the independent variables from two categories: 5 bank-specific factors and 3 macroeconomic factors. In order to overcome unobservable and constant heterogeneity as well as endogeneity problem, this paper use the system GMM estimator. According to our findings, the most variables are significantly related to bank performance, except the size of banks and the unemployment rate.